Retirement and the qnnuity puzzle: how vital are health conditions? - Silva, Rodrigo Luz e (2024)
This study aims to assess the Annuity Puzzle and its interplay with health statuses, taking into account, for instance, health cost risk, liquidity, poor health, and adverse selection. The motivation is associated with the fact that contrary to economic theory, most individuals choose to retire without lifetime retirement income. A body of work has focused on the relevance of health to this annuitization conundrum, finding mixed results. Whereas most of the literature focused on the U.S. context, this study intends to emphasize a Brazilian setting, where private voluntary health insurance (VHI) and out-of-pocket (OOP) expenses with medications, nursing home, medical equipment, and other uncovered procedures may impose a burdensome economic hardship, despite the existence of universal health coverage (UHC). The combined use of health and pension indicators is intended in a computational model simulation approach, as data concerning individuals annuitization choices are scarce. To that end, a review of the framework of the Frailty Index, the Disability Adjusted Life Year (DALY), the Moneys Worth Ratio (MWR) is provided.